Police discretion to charge young people who use drugs prior to cannabis legalization in British Columbia, Canada: a brief report of quantitative findings. (1st November 2020) - Greer, Alissa; Sorge, Justin; Selfridge, Marion; Benoit, Cecilia; Jansson, Mikael; Macdonald, Scott
Abstract: Introduction: Normalization theory posits a process where drug use is socially accommodated in society. We examine the extent of and factors related to police decision to charge young people who use drugs prior to cannabis legalization in Canada in 2018 and situate these findings within normalization theory. Methods: In the Youth Experiences with Police study, young people (aged 16–30 years) who use drugs from three cities in British Columbia, Canada, were recruited using a modified respondent driven sampling approach. Participants were administered a questionnaire focusing on their drug use, past encounters with police, and psychosocial and sociodemographic factors. Results: Among 449 participants, 3.6% of 56 in possession of cannabis by police were charged, whereas 41.2% of 34 in possession of other illicit drugs were charged ( p < .001). Bivariate analyses showed prior criminal convictions ( p = .001) as well as lower average monthly income ( p < .05) was significantly related to being charged by police. Drug use stigma was significantly higher for weekly illicit drug users compared to weekly cannabis and those who did not use drugs weekly ( p < .001). Discussion: Greater police discretion toward cannabis suggest it is more socially acceptable or normalized compared to other drugs. Police practices may reflect cultural conditions but could be structurally harmful to marginalized groups.